а) C2H4-->C2H5OH-->CH3COOH-->CH3COOСH3-->CH3COONa
C2H4 + H2O == C2H5OH
3C2H5OH + 2K2Cr2O7 + 8H2SO4 ==3CH3COOH + 2K2SO4 + 2Cr2(SO4)3 +
+ 11H2O
CH3COOH + CH3OH == CH3COOCH3 + H2O
CH3COOCH3 + NaOH = CH3COONa + CH3OH
б) C3H6-->C3H7OH-->C2H5COOH-->C2H5COOC2H5-->C2H5COOK
C3H6 + H2O == C3H7OH
3C3H7OH + 2K2Cr2O7 + 8H2SO4==3C2H5COOH + 2K2SO4 + 2Cr2(SO4)3 +
C2H5COOH + C2H5OH == C2H5COOC2H5 + H2O
C2H5COOC2H5 + KOH == C2H5COOK + C2H5OH
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
а) C2H4-->C2H5OH-->CH3COOH-->CH3COOСH3-->CH3COONa
C2H4 + H2O == C2H5OH
3C2H5OH + 2K2Cr2O7 + 8H2SO4 ==3CH3COOH + 2K2SO4 + 2Cr2(SO4)3 +
+ 11H2O
CH3COOH + CH3OH == CH3COOCH3 + H2O
CH3COOCH3 + NaOH = CH3COONa + CH3OH
б) C3H6-->C3H7OH-->C2H5COOH-->C2H5COOC2H5-->C2H5COOK
C3H6 + H2O == C3H7OH
3C3H7OH + 2K2Cr2O7 + 8H2SO4==3C2H5COOH + 2K2SO4 + 2Cr2(SO4)3 +
+ 11H2O
C2H5COOH + C2H5OH == C2H5COOC2H5 + H2O
C2H5COOC2H5 + KOH == C2H5COOK + C2H5OH